2013
DOI: 10.1111/bcp.12141
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral selectivity of the novel cannabinoid receptor antagonist TM38837 in healthy subjects

Abstract: Aim Cannabinoid receptor type 1 (CB1) antagonists show central side effects, whereas beneficial effects are most likely peripherally mediated. In this study, the peripherally selective CB1 antagonist TM38837 was studied in humans. Methods This was a double‐blind, randomized, placebo‐controlled, crossover study. On occasions 1–4, 24 healthy subjects received 5 × 4 mg THC with TM38837 100 mg, 500 mg or placebo, or placebos only. During occasion 5, subjects received placebo TM38837 + THC with rimonabant 60 mg or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 28 publications
0
50
0
1
Order By: Relevance
“…These compounds exhibited CB1 receptor antagonistic activity equal to or less than 10 µM. (147)(148)(149) Maitra et al [126] invented novel peripherally restricted diphenyl purine derivatives that did not cross the BBB and thus minimized CNS-related side effects. Compound (150) exhibited a K i value of 0.355 µM with CB1/CB2 ratio of 30.2.…”
Section: Purine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds exhibited CB1 receptor antagonistic activity equal to or less than 10 µM. (147)(148)(149) Maitra et al [126] invented novel peripherally restricted diphenyl purine derivatives that did not cross the BBB and thus minimized CNS-related side effects. Compound (150) exhibited a K i value of 0.355 µM with CB1/CB2 ratio of 30.2.…”
Section: Purine Derivativesmentioning
confidence: 99%
“…Further development of compounds of this class may be beneficial for the pharmacotherapy of this metabolic disorder. Another company 7TM Pharma [147] has also identified compound TM38837 [148], a second-generation CB1 receptor antagonist that acts peripherally [149] and has the potential to treat several metabolic disorders without CNS side effects. In 2010, the company announced that they have successfully conducted and completed Phase I clinical trials of compound TM38837 for the treatment of obesity and related metabolic disorders [147] and this type of compound should be further developed.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Typically, systemic administration of cannabinoids evokes a depressor and bradycardic response (32, 35, 58), attributed, in part, to activation of peripheral CB 1 Rs on autonomic nerves innervating the heart and on sympathetic nerves innervating the vascular smooth muscle. Yet, in humans, the prominent and most consistent response to the cannabinoid Δ 9 -tetrahydrocannabinol (THC) is a CB 1 R-dependent increase in heart rate (25, 30). This tachycardia, which is usually accompanied by a small increase in blood pressure and an increase in cardiac output, is attributed to an increase in cardiac sympathetic nerve activity and a decrease in cardiac parasympathetic nerve activity (2).…”
mentioning
confidence: 99%
“…This tachycardia, which is usually accompanied by a small increase in blood pressure and an increase in cardiac output, is attributed to an increase in cardiac sympathetic nerve activity and a decrease in cardiac parasympathetic nerve activity (2). While there is evidence for the involvement of peripheral CB 1 Rs in the increase in heart rate (30, 55), many studies support a centrally mediated contribution (3, 27, 43). Recent studies suggest that central administration of cannabinoids primarily evokes a sympathoexcitatory and vagal inhibitory response mediated by CB 1 Rs.…”
mentioning
confidence: 99%
“…7TM Pharma discovered diaryl pyrazole TM38837 (b), a peripherally acting CB1 receptor antagonists which showed a brain-to-plasma ratio of 1:33 [16]. The data suggested that a 100-mg dose of TM38837 did not show any central nervous system (CNS) side effects as it did not enter into the brain [17]. Similarly, AM6545 (c), a diaryl pyrazole derivative, offered very promising results as peripheral CB1 receptor antagonist [18].…”
Section: Introductionmentioning
confidence: 99%